New insights into the effect of extracellular polymeric substance on the sludge dewaterability based on interaction energy and viscoelastic acoustic response analysis. (December 2020) - Lin, Feng; Li, Jigeng; Liu, Mengru; Yu, Peiran; Zhang, Zhanbo; Zhu, Xiaolin
Abstract: To elucidate the effects of extracellular polymeric substance (EPS) on the sludge dewaterability, this study comparatively investigated the changes in EPS composition and spatial distribution, together with the sludge dewaterability after lysozyme (LZM) conditioning. The protein concentration in the tightly bound EPS (TB-EPS) increased from 3.47 mg g −1 DS to 4.99 mg g −1 DS within the first 2 min, then gradually decreased, which could be described by a piecewise linear function. Unlike TB-EPS, the protein content variation trend in both soluble EPS (S-EPS) and loosely bound EPS (LB-EPS) followed the typical first-order kinetics. Additionally, the extended DLVO theory was employed in combination with viscoelastic acoustic response analysis to further explore the impact of EPS composition on water adhesion and microbial cell. After the extraction of S-EPS from the conditioned sludge, the adsorption free energy (ΔGadh ) of EPS ascended to −61.05 mJ m −2, indicating the weakened microbial hydrophobicity. By contrast, the ΔGadh value declined after the subsequent extraction of LB-EPS and TB-EPS. Meanwhile, the adsorption potential energy between S-EPS and microbial cells showed an increasing trend, whereas the repulsion potential energy between TB-EPS and microbial cells fell to 1.40 × 10 4  kT, signifying a weakened adsorption capacity to water. Accordingly, the viscosity and shear modulus of each EPS layer were reduced after conditioning, which contributed to the transformation of bound water into free water. These changes reasonably explained the results that the water content in the dewatered sludge after conditioning was reduced to 58.54%, and the bound water content decreased by 15.06%. Graphical abstract: Image 1 Highlights: The change of TB-EPS was described by piecewise function after LZM conditioning. Protein substances in EPS were largely responsible for sludge dewatering. The hydrophobicity of the enzyme-treated sludge was improved. Reduction of repulsion between TB-EPS and cell weaken the absorption of EPS to water. The reduction of EPS viscosity and shear modulus was conducive to sludge dewatering.